Basic relationship formulation of the sundatang physical characteristics - Ronald Yusri Batahong; Jedol Dayou (e-VIBS, Faculty of Science and Natural Resources, 2016)
Sundatang is one of the traditional musical instruments which were made based from natural resources in the land of Sabah. The instrument which belongs to the Kadazan, Dusun and Rungus communities ought to be conserved and upgraded to make it popular and well-accepted among the new generation in this state and generally throughout the world. The purpose of this study was to formulate the basic relationship of the physical characteristics of sundatang. To achieve this, several important dimensions were measured from four units of sundatangs. The measured physical characteristics were scrutinized, analyzed and compared to obtain general physical characteristics of sundatang. Four basic relationship equations of the physical characteristics were formulated which are related to the length of sundatang, distance of frets, height of frets and width of sundatang. The formulated equations can be used to calculate the intended physical dimensions in the making process of sundatang. It is also very important to the advancement of construction technique study of sundatang in future.